Міжнародний досвід державного управління в галузі охорони навколишнього середовища і раціонального природокористування - Пугач, Андрій Миколайович; Pugach, A.; Марениченко, Валерий Валентинович; Marenichenko, V. (Харкiвський регiональний iнститут державного управлiння, 2019)
Досліджено міжнародний досвід охорони навколишнього природного середовища і раціонального використання природних ресурсів в ракурсі національних програм; виділено екологічні угоди як інструмент державного управління в галузі охорони навколишнього середовища; визначено основні форми саморегуляції промисло-вості в галузі екологічної політики; проаналізовано правове регулювання охорони навколишнього природного середовища країн ЄС; обґрунтовано пріоритетні заходи в міжнародній практиці охорони навколишнього середовища і раціонального природокористування. The international experience of environmental protection and rational use of natural resources in the perspective of national programs is researched. In particular, the National Programs have been identified: USA The US Wetlands Action Plan (US Fish & Wildlife Service, 1990), The US Environment Protection Agency and Army Corps of Engineers (Lynch-Stewart, 1992); Netherlands – Danish «no loss» wetlands policy (Moller, 1995); EU – European Union principles for the implementing a no net loss policy (Commission of the European Communities, 1995). Environmental agreements as an instrument of state governance in the field of environmental protection have been identified. In particular, the agreements that cover different problem areas, such as reducing the environmental impact of existing sources pollution, reduction of toxic substances, the content of harmful substances in products, to prevent the formation and recycling of waste and others are defined. The basic forms of industrial self-regulation in the field of environmental policy are determined. In particular, there is definition that the standard form of self-regulation of industry in the field of environmental policy is self-commitments, not formal agreements in Germany. The legal regulation of environmental protection of EU countries is analyzed. In particular, it is determined that in the laws of European countries environmental protection is considered as an integral part of socio-economic policy, but the priority in the protection of certain natural objects is different. The priority measures in the international practice of environmental protection and rational use of natural resources are substantiated. In particular, it should be highlighted among them, such as the introduction of a mechanism for the decommissioning of public debt in exchange for environmental improvements («nature debts»); creation of model centers of balanced.
International experience of state governance in the field of environmental protection and rational environmental consumption
Keywords: державне управління; state governance; навколишнє середовище; environment; охорона; protection; раціональне природокористування; rational environmental consumption